2021
DOI: 10.3389/fmed.2021.711973
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Technology for the Personalized Therapy of Hemophilia

Abstract: The management of patients with hemophilia has evolved significantly since the first treatment attempts were made in the late 1930s. Since then, each new step in the treatment of patients with hemophilia has brought important advancements, as well as its unique set of challenges. Today, a patient-centered, individualized comprehensive approach is the new paradigm, moving away from the traditional “one size-fits-all” approach, to provide the best possible care for each patient with a bleeding disorder. As part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[2][3][4] These technologies are being evaluated for a range of clinical purposes, such as disease screening and monitoring as well as health behaviors associated with, recovery, disease management, and compliance with treatment regimens. [5][6][7][8] In parallel, mHealth interventions are being evaluated to promote and sustain healthy behaviors through approaches like daily monitoring, reminders and education to maintain well-being and wellness. [9][10][11][12] Some wearables are approved by the US Food and Drug Administration (FDA) as clinical devices, though accessible through retail stores without a prescription.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] These technologies are being evaluated for a range of clinical purposes, such as disease screening and monitoring as well as health behaviors associated with, recovery, disease management, and compliance with treatment regimens. [5][6][7][8] In parallel, mHealth interventions are being evaluated to promote and sustain healthy behaviors through approaches like daily monitoring, reminders and education to maintain well-being and wellness. [9][10][11][12] Some wearables are approved by the US Food and Drug Administration (FDA) as clinical devices, though accessible through retail stores without a prescription.…”
Section: Introductionmentioning
confidence: 99%
“…It also helps haemophilia parents and patients to adjust the treatment process. 12 Although technology-assisted interventions are considered to be helpful for caregivers of children with coagulation factor deficiencies, only a limited number of studies have used psychosocial and educational interventions in caregivers of children with haemophilia. It was reported that providing this intervention by haemophilia care centres improved parents outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Mobile health applications have an important role in access to patient-centred care. 12 Using mobile technology empowered haemophilia patients to modify their lifestyle, receive peer support and increase adherence to care and treatment. 13 Using social network groups especially during COVID-19 pandemic provided opportunities of interaction between haemophilia patients, parents/caregivers and healthcare professionals (HCPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For social mobilization, the National Hemophilia Foundation of Thailand in cooperation with the Thai Hemophilia Patient Club are actively promoting self-engagement and use of digital technology, i.e., smartwatch monitoring and hemophilia mobile applications, to foster improvement of aerobic exercise capacity and muscle strength among Thai hemophiliacs during the age of digital technology [ 10 ]. A study to evaluate the impact of increased physical activities monitored by these modalities during low-dose CFC prophylaxis in Thai hemophiliacs is ongoing (ClinicalTrials.gov NCT05728528).…”
mentioning
confidence: 99%